Moral Competence and Aggression Prevention. Updating MCT Pilot Studies Inspired by Georg Lind’s Book How to Teach Morality. Promoting Deliberation and Discussion, Reducing Violence and Deceit (2016) - Nowak, Ewa; Urbańska, Adrianna (ETHICS IN PROGRESS, 2017)
Aggression in juveniles may increase even in modern societies and manifest itself in countless forms of violence, including harming, persecution, abuse, pressure, hostility, etc. A large number of studies on the evolutionary, psychological and sociological origins of aggression are available. However, we lack cognitive remedies to counter developing tendencies towards aggressive behavior. Georg Lind's book How to teach morality. Promoting deliberation and discussion, reducing violence and deceit (2016) offers such a remedy based on his long–term (1976–2017) experiences with dilemma discussion training. This paper draws on Lind's conception of strengthening socio-moral competence as the most efficient remedy against aggression. It also revisits the ongoing theories of empathy. Finally, it revises the pilot research study that we conducted 2010 among Polish and Swiss juveniles7. That study focused on the following hypotheses: Lind's method of dilemma discussion (KMDD) can train and retrain moral competence in  uveniles that show a slight inclination towards aggressive behavior. Strong moral competence may prevent further maldevelopment, in particular interpersonal and collective violence.